Metode Call-To-Action dalam Unggahan @hopeishere.id terhadap Minat Berkonsultasi melalui Layanan Konseling - Halwa Khairani; Wahyu Budi Priatna; Rici Tri Harpin Pranata; Sutisna Riyanto (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Social media, especially Instagram, has been widely used by individuals and communities to expand the campaigns they run. Mental health communities such as the House of Psyche (HOPE) through the Instagram account @hopeishere.id are no exception. HOPE provides online mental health counseling services with centralized promotion on social media. This study aims to find out the strength of Call-To-Action (CTA) relationships in @hopeishere.id uploads as well as the most dominant factors that affect followers' interest in consulting. This study uses a quantitative approach with a survey method. Respondents consisted of 33.3% men and 66.7% women, with 38.4% of the total respondents having consulted through HOPE counseling services. The results showed that CTA had a positive relationship with interest in consulting with a connectivity rate of 62%. It is known that the correlation coefficient (r) is 0.788; while the significance was < 0.001 (p < 0.05). These findings confirm that evocative sentences and positive testimonials bring high success in improving the mental well-being of @hopeishere.id followers.